High-speed optical recording in vitreous chalcogenide thin films - Kryuchyn, A.A.; Petrov, V.V.; Rubish, V.M.; Lapchuk, A.S.; Kostyukevych, S.O.; Shepeliavyi, P.E.; Kostyukevych, K.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Thin films of glassy chalcogenide semiconductor are widely used as recording media in optical data storage. To obtain relief micro- and nanoscale structures on the surface of optical master discs inorganic photoresists based on chalcogenide glassy semiconductors can be used. They have high resolution and allow for exposure by short laser pulses. Implementation of such exposure is promoted by increasing the speed of photostructural transformations at high powers of exposing radiation. This increase in the sensitivity is associated with both local heating by illumination and a high density of excited electron-hole pairs. The exposure mode of the inorganic photoresists based on glassy chalcogenide semiconductor pulses of 10⁻⁸-10⁻⁹ s is close to the threshold of local photothermal destruction. Significant impact on the value of the threshold of photothermal destruction effects the choice of the substrate material which determines the rate of heat removal from the irradiation area. Moreover, one also needs to consider the effect of pulsed annealing of the inorganic photoresist material on the process of selective etching. We have established an inversion of the selective etching of the inorganic negative photoresist based on As₂S₃ in the center of the irradiated zone. The diameter of this zone is about 20% of the diameter of exposing beam. After the selective etching in alkaline solution in the center of protrusions being formed on the substrate, there observed are some dimples with the depth of 30-50 nm. Prior to the processing of irradiated inorganic photoresist by the selective etching these dimples were absent and their appearance is not due to possible local material evaporation of the inorganic photoresist. A possible reason for the inversion of solubility of the inorganic photoresist could be pulsed annealing in the recording process.